The association of a scholarly concentrations program with medical students’ matched residencies - Hosam H. Alkhatib; Mary Catherine Beach; Kelly A. Gebo; Eric B. Bass; Jenny R. Park; Meredith A. Atkinson; Sapna R. Kudchadkar; Stephen M. Sozio (Medical Education Online, 2023)
ABSTRACTPurpose Many medical school curricula include Scholarly Concentrations (SC) programs. While studies have examined how these programs affect students’ future research involvement, the association of SC programs with students’ specialty choices is uncertain. This study examines the SC program factors associated with congruence between the specialty focus of students’ SC projects and the clinical specialty they matched into for residency.Methods The authors conducted a retrospective cohort study of all students participating in the SC program at Johns Hopkins University School of Medicine for graduating classes 2013–2020. They used data from program questionnaires to categorize students’ specialty interests (baseline) and SC program experiences (post-program). The authors categorized each student’s project into specialties according to their faculty mentors’ primary appointments, abstracted student publications from SCOPUS, and abstracted residency program rankings from Doximity Residency Navigator. The authors used multivariable logistic regression to calculate adjusted odds ratios (aOR) for specialty-congruent matching (same specialty as SC project) and for matching into a Doximity-ranked top 20 or top 10 program.Results Overall, 35.3% of the 771 students matched into the same specialty as their SC projects. Increased odds of specialty-congruent matching occurred with ‘definite’ interest in the specialty at baseline [aOR (95% CI): 1.76 (0.98–3.15)] (P = 0.06) and with increasing publications with SC mentors [aOR (95% CI): 1.16 (1.03–1.30)] (P = 0.01). Congruence between SC specialty focus and matched specialty conferred no significant difference in odds of matching to a Doximity-ranked top 20 or top 10 program.Conclusions Baseline certainty of specialty interest and research productivity were associated with specialty congruence. However, as completing an SC project in a given specialty was not associated with increased odds of matching into that specialty nor into a higher Doximity-ranked program, SC program directors should advise students to pursue SC projects in any topic of personal interest.